2022
DOI: 10.20944/preprints202210.0194.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Blood-Brain Barrier Transport of Transferrin-Receptor Targeted Nanoparticles

Abstract: The blood-brain barrier (BBB), built by brain endothelial cells (BECs), is impermeable to biologics. Liposomes and other nanoparticles are good candidates for delivery of biologics across the BECs, as they can encapsulate numerous molecules of interest in an omnipotent manner. The liposomes need attachment of a targeting molecule, as BECs unfortunately are virtually incapable of uptake of non-targeted liposomes from the circulation. Experiments of independent research groups have qualified antibodies targeting… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Recent advances allowed monitoring of AMT at unprecedented details in vivo, i.e., at different categories of cerebral microvessels and at the level of single transport vesicles in the living brain (Mathiesen Janiurek et al, 2019;Kucharz et al, 2021;Thomsen et al, 2022). Here, using 2 PM, we found that AMT was unchanged in 5xFAD mice compared to the WT, regardless of the vessel type.…”
Section: Discussionmentioning
confidence: 54%
“…Recent advances allowed monitoring of AMT at unprecedented details in vivo, i.e., at different categories of cerebral microvessels and at the level of single transport vesicles in the living brain (Mathiesen Janiurek et al, 2019;Kucharz et al, 2021;Thomsen et al, 2022). Here, using 2 PM, we found that AMT was unchanged in 5xFAD mice compared to the WT, regardless of the vessel type.…”
Section: Discussionmentioning
confidence: 54%
“…Tf has been extensively researched as a potential probe for drug delivery targeting, due to its ability to target drugs to the blood and cerebrospinal fluid barriers. The transferrin receptor (TfR) has long been a widely studied therapeutic target, as it is highly expressed in nerve cells and cerebrovascular epithelial cells (THOMSEN et al, 2022). Utilizing endogenous ligands Tf or antibodies against Tf Frontiers in Pharmacology frontiersin.org enables drug targeting through TfR-mediated cellular uptake, effectively facilitating drug accumulation in the brain (BIEN-LY et al, 2015).…”
Section: Tfmentioning
confidence: 99%
“…Receptor-mediated transport is another possible mechanism, in which an NBT is conjugated with a ligand specific to a receptor present in brain endothelial cells. One method by which receptormediated transport is exploited for drug delivery to the brain is targeting the transferrin receptor (Tfr1) abundant on brain endothelial cells (Thomsen et al, 2022).…”
Section: Bbb Uptake Mechanismsmentioning
confidence: 99%